2023
DOI: 10.3390/pathogens12030437
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Interferon Responses at the Ocular Surface in Herpes Simplex Virus-1-Induced Herpetic Stromal Keratitis

Abstract: Herpes simplex virus type 1 (HSV-1) is a highly successful pathogen that primarily infects epithelial cells of the orofacial mucosa. After initial lytic replication, HSV-1 enters sensory neurons and undergoes lifelong latency in the trigeminal ganglion (TG). Reactivation from latency occurs throughout the host’s life and is more common in people with a compromised immune system. HSV-1 causes various diseases depending on the site of lytic HSV-1 replication. These include herpes labialis, herpetic stromal kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 376 publications
0
7
0
Order By: Relevance
“…Therefore, we concentrated on researching how the HSV-1 gene ICP27 affects hTert-RPE 1 cells' AIM 2 inflammasome pathway. Not only are hTert-RPE 1 cells target cells during primary HSV-1 infection at the ocular level, but they also modulate the immune response by releasing a variety of cytokines that affect the inflammatory response of neighboring immune cells, including macrophages, dendritic cells, and NK cells, which are located close to the retinal epithelial barrier [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concentrated on researching how the HSV-1 gene ICP27 affects hTert-RPE 1 cells' AIM 2 inflammasome pathway. Not only are hTert-RPE 1 cells target cells during primary HSV-1 infection at the ocular level, but they also modulate the immune response by releasing a variety of cytokines that affect the inflammatory response of neighboring immune cells, including macrophages, dendritic cells, and NK cells, which are located close to the retinal epithelial barrier [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that endosomal and cytoplasmic Pattern Recognition Receptors and the cell surface recognize HSV and as such start a cascade of immune response which includes Interferons (IFN), Chemokine, and Cytokine production as well as the recruitment of other inflammatory cells to the location of the infection[ 94 ]. IFN-1 release in acute HSV keratitis limits dendritic lesion enlargement[ 95 ].…”
Section: Understanding the Pathogenesis Of Herpes Simplex Keratitismentioning
confidence: 99%
“…Various cell types contribute to the innate immune response in both mucosal epithelia and the nervous system, providing additional support and protection during α-HV invasion [8,22,26]. Some of these cells include neutrophils, plasmacytoid dendritic cells (pDCs), and natural killer (NK) cells [27][28][29][30]. These cells play a vital role in the antiviral response partly due to their role in the synthesis and production of cytokines.…”
Section: Basics Of Intrinsic and Innate Immunity Against Alpha Herpes...mentioning
confidence: 99%